2007
DOI: 10.1099/vir.0.82342-0
|View full text |Cite
|
Sign up to set email alerts
|

PrPCWD in rectal lymphoid tissue of deer (Odocoileus spp.)

Abstract: The utility of rectal lymphoid tissue sampling for the diagnosis of chronic wasting disease (CWD) infections in mule deer (Odocoileus hemionus) and white-tailed deer (Odocoileus virginianus) was evaluated. CWD-associated prion protein (PrPCWD) deposits were observed in the rectal mucosa from 19 orally inoculated mule deer by 381 days post-inoculation (p.i.); similarly, 45 out of 50 naturally infected mule deer had PrPCWD in their rectal mucosa. In orally inoculated white-tailed deer, the presence of glycine (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 18 publications
3
94
0
Order By: Relevance
“…Post-mortem detection of PrP d in the RAMALT was achieved in a low percentage [13]), and similar ones in chronic wasting disease of cervids [21,33]. Whether this is a feature of goat scrapie in general or a peculiarity of this outbreak is unknown but, in any case, the frequency of detection of PrP d in the RAMALT rises to 84.0% when goats with widespread LRS involvement -but still at preclinical stagesare considered.…”
Section: Implications For Surveillance Of Goat Tsementioning
confidence: 75%
“…Post-mortem detection of PrP d in the RAMALT was achieved in a low percentage [13]), and similar ones in chronic wasting disease of cervids [21,33]. Whether this is a feature of goat scrapie in general or a peculiarity of this outbreak is unknown but, in any case, the frequency of detection of PrP d in the RAMALT rises to 84.0% when goats with widespread LRS involvement -but still at preclinical stagesare considered.…”
Section: Implications For Surveillance Of Goat Tsementioning
confidence: 75%
“…Candidate parents harvested in the 2002 season with obex + or obex ++ positive were categorized as CWD-positive at breeding. Candidate parents harvested in the 2003 season with obex + positive were categorized as CWD-negative at breeding because PrP CWD accumulation in the obex generally occurs within 12 mo after infection (Sigurdson et al, 1999;Fox et al, 2006) 2006; Johnson et al, 2006;Wolfe et al, 2007;Johnson et al, 2011). There are no specific data published, however, about how CWD progresses over time in the different Prnp genotypes in white-tailed deer except for time to clinical disease and death (Wilson et al, 2009;Johnson et al, 2011).…”
Section: Cwd Status At Breedingmentioning
confidence: 99%
“…In naturally infected white-tailed deer, deer that expressed 96SS PrP had a lower risk for CWD infection, but were not resistant, since at least three of 7350 CWD infected deer were positive for PrP Sc in brain [36,59]. Other studies suggest that the 96S allele delays CWD disease progression [95]. Perhaps these two allelic genotypes select for different CWD strains.…”
Section: The Cervid Prnp Genementioning
confidence: 99%
“…PrP Sc was readily detected by IHC in rectal lymphoid follicles from experimentally infected deer, where 19 of 19 deer were positive by one year after oral inoculation. In naturallyinfected mule deer, 45 of 50 subclinical and terminal CWD-infected deer, as determined by immunohistochemistry on tonsil or retropharyngeal lymph nodes, were also positive by rectal biopsy [95]. Rectal biopsies to diagnose CWD in elk may also be suitable, as one study showed a strong correlation between tonsil, rectal mucosa, and brain in CWD positive elk, although one of seven elk with early CWD was tonsil positive, but rectal mucosa negative [82].…”
Section: Cwd Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation